2017
DOI: 10.1111/jcmm.13179
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin gallate inhibits Streptococcus pneumoniae virulence by simultaneously targeting pneumolysin and sortase A

Abstract: Streptococcus pneumoniae (pneumococcus), the causative agent of several human diseases, possesses numerous virulence factors associated with pneumococcal infection and pathogenesis. Pneumolysin (PLY), an important virulence factor, is a member of the cholesterol‐dependent cytolysin family and has cytolytic activity. Sortase A (SrtA), another crucial pneumococcal virulence determinate, contributes greatly to the anchoring of many virulence‐associated surface proteins to the cell wall. In this study, epigallocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 52 publications
(91 reference statements)
2
47
0
Order By: Relevance
“…CMDA and mutational analysis predicted that EGCG binds to Glu277, Tyr358, and Arg359 in PLY and Thr169, Lys171, and Phe239 in SrtA ( Figure 9 ). Since EGCG protected mice against pneumonia by S. pneumoniae , EGCG may be a promising therapeutic option for this disease [ 91 ].…”
Section: Cmda Of Catechin-protein Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…CMDA and mutational analysis predicted that EGCG binds to Glu277, Tyr358, and Arg359 in PLY and Thr169, Lys171, and Phe239 in SrtA ( Figure 9 ). Since EGCG protected mice against pneumonia by S. pneumoniae , EGCG may be a promising therapeutic option for this disease [ 91 ].…”
Section: Cmda Of Catechin-protein Interactionmentioning
confidence: 99%
“…CMDA predicts the involvement of Ser256, Glu277, Tyr358, and Arg359 in PLY and Thr167, Lys169, and Phe237 in SrtA in the binding to EGCG. Reproduced from [ 91 ] under the terms of the Creative Commons Attribution License (CC BY).…”
Section: Figurementioning
confidence: 99%
“…The various PLY antagonists identified, none of which was found to possess antimicrobial activity, effectively attenuated the hemolytic activity of PLY, as well as the injurious effects of the toxin on an alveolar epithelial cell line in vitro [ 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ]. In addition, subcutaneous administration of these various natural antagonists of PLY resulted in significantly improved survival in a murine model of intranasal pneumococcal lung infection [ 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ]. The various members of each category of natural antagonists of PLY are summarized as follows: phytosterols : β-sitosterol was initially identified as a cholesterol-mimic, interacting with the conserved cholesterol-binding site located on domain 4 of PLY, with potency comparable with that of cholesterol [ 99 ].…”
Section: Update On Pneumolysin-targeted Therapeutic Strategiesmentioning
confidence: 99%
“…A follow-up, mechanistic study, using a molecular dynamics simulation approach, revealed two additional phytosterols which also antagonized the membrane-binding activity of PLY viz. campesterol and brassicasterol, with the former demonstrating activity comparable with that of β-sitosterol and the latter being somewhat less potent [ 100 ] polyphenols : verbascoside (a caffeoyl polyethanol glycoside) and the catechin, epigallocatechin gallate, are naturally-occurring polyphenol anti-oxidant antagonists of PLY, which have demonstrated almost complete attenuation of the hemolytic activity of the toxin at concentrations of about 2.0 and 2.7 µg/mL respectively [ 101 , 102 ]. Unlike the phytosterols, the polyphenol antagonists appear to interfere with the oligomerization of PLY monomers on the target cell membrane via binding to the cleft between domains 3 and 4 of the toxin molecule [ 101 , 102 ] bioflavonoids : three bioflavonoids viz.…”
Section: Update On Pneumolysin-targeted Therapeutic Strategiesmentioning
confidence: 99%
See 1 more Smart Citation